Metodologia pró-MaDiMM para desenvolvimento de materiais didáticos multimídia - Mansano Neto, João (2003)
Generally speaking, didactic materials, of different types, have helped lecturers and students during the endeavouring teaching-learning process. Informatics and computer techniques have brought into context several alternatives that can facilitate the production, in terms of improved performance and quantity, of this kind of materials. Students, agents and subjects of the informatics influences, have been claiming a novel approach towards the teaching process, demanding more creative and innovative educational strategies and resources. There are various signs that lectures have been realising this trend and have been seeking, through informatics and simple pieces of software, means for helping them in their daily activities. Additionally, lecturers have been avoiding low level programming languages, mainly because these resources demand great effort (i.e. time and training), despite producing more elaborated materials. Therefore, there are several evidences that certain assertive factors/elements, such as mentioned above, can lead to a promising multimedia didactic materials. However, these factors are not well connected. This research aims at identifying and evaluating these potentialelements that can contribute to motivating the creation of multimedia didactic materials. The scheme adopted to develop such materials is based on the product design approaches, available in literature. From the information gathered a novel methodology is proposed, whichguides the development of multimedia didactic materials, inside the working environment (i.e.schools, universities), by lecturers themselves. Additionally, the procedures and tools systematise and provide a follow up to the whole process. The methodology has been assessed via a validation and experimental mechanisms. The data obtained from potential multimedia didactic materials developers, through thispreliminary evaluation stage, has provided several useful insights upon the promising applications of the structure and techniques suggested.